Phase II Randomized Study of Salvage Radiation Therapy Plus Enzalutamide or Placebo for High-Risk Prostate-Specific Antigen Recurrent Prostate Cancer After Radical Prostatectomy: The SALV-ENZA Trial. Issue 6 (20th February 2023) - Tran, Phuoc T.; Lowe, Kathryn; Tsai, Hua-Ling; Song, Daniel Y.; Hung, Arthur Y.; Hearn, Jason W.D.; Miller, Steven; Proudfoot, James A.; Deek, Matthew P.; Phillips, Ryan; Lotan, Tamara; Paller, Channing J.; et al.
Abstract : PURPOSE: We sought to investigate whether enzalutamide (ENZA), without concurrent androgen deprivation therapy, increases freedom from prostate-specific antigen (PSA) progression (FFPP) when combined with salvage radiation therapy (SRT) in men with recurrent prostate cancer after radical prostatectomy (RP). PATIENTS AND METHODS: Men with biochemically recurrent prostate cancer after RP were enrolled into a randomized, double‐blind, phase II, placebo-controlled, multicenter study of SRT plus ENZA or placebo (ClinicalTrials.gov identifier: NCT02203695 ). Random assignment (1:1) was stratified by center, surgical margin status (R0 v R1), PSA before salvage treatment (PSA ≥ 0.5 v < 0.5 ng/mL), and pathologic Gleason sum (7 v 8‐10). Patients were assigned to receive either ENZA 160 mg once daily or matching placebo for 6 months. After 2 months of study drug therapy, external-beam radiation (66.6‐70.2 Gy) was administered to the prostate bed (no pelvic nodes). The primary end point was FFPP in the intention-to-treat population. Secondary end points were time to local recurrence within the radiation field, metastasis‐free survival, and safety as determined by frequency and severity of adverse events. RESULTS: Eighty-six (86) patients were randomly assigned, with a median follow-up of 34 (range, 0-52) months. Trial arms were well balanced. The median pre-SRT PSA was 0.3 (range, 0.06-4.6) ng/mL, 56 of 86 patients (65%) had extraprostatic disease (pT3), 39 of 86 (45%) had a Gleason sum of 8-10, and 43 of 86 (50%) had positive surgical margins (R1). FFPP was significantly improved with ENZA versus placebo (hazard ratio [HR], 0.42; 95% CI, 0.19 to 0.92; P = .031), and 2-year FFPP was 84% versus 66%, respectively. Subgroup analyses demonstrated differential benefit of ENZA in men with pT3 (HR, 0.22; 95% CI, 0.07 to 0.69) versus pT2 disease (HR, 1.54; 95% CI, 0.43 to 5.47; P interaction = .019) and R1 (HR, 0.14; 95% CI, 0.03 to 0.64) versus R0 disease (HR, 1.00; 95% CI, 0.36 to 2.76; P interaction = .023). There were insufficient secondary end point events for analysis. The most common adverse events were grade 1-2 fatigue (65% ENZA v 53% placebo) and urinary frequency (40% ENZA v 49% placebo). CONCLUSION: SRT plus ENZA monotherapy for 6 months in men with PSA-recurrent high-risk prostate cancer after RP is safe and delays PSA progression relative to SRT alone. The impact of ENZA on distant metastasis or survival is unknown at this time.